THE EFFECT OF KOOPERATIF LEARNING MODEL TYPE GROUP INVESTIGATION AND FIRST CONCEPT UNDERSTANDING TO SCIENCE PROCESS SKILL OF SENIOR HIGH SCHOOL STUDENT - Hiba Dertyana Siregar; Motlan . (Jurnal Pendidikan Fisika, 2016)
This study aims to: know the difference science process skills of students using cooperative learning model group investigation with direct instruction teaching model. This study is quasi exsperiment. The sample in this research was done by using cluster random sampling two classes. Instruments used in this research is understanding the concept of the initial test in the form of multiple-choice comprised of 10 questions and test science process skills in the form of 15 questions of multiple choice. From the results of this study concluded that: 1) there are differences in students' science process skills are taught using cooperative learning model group investigation, 2) there is a difference science process skills of students who have an understanding of the concept of high and low initial, 3) there is an interaction between the model of cooperative learning group investigation and understanding of the initial concept of the science process skills that students have a better learning model applied to students who have an understanding of the high initial concept.